EFFECT OF STABILIZING EXERCISES AND ACUPUNCTURE ON POSTPARTUM SACROILIAC PAIN IN EGYPTIAN FEMALES: A RANDOMIZED CONTROL TRIAL (International Journal of Physiotherapy, 2016)
Background: Postpartum sacroiliac joint pain, is a serious problem for the mother, affect the ability to perform daily activities and minimize health-related quality of life. This study aimed to determine the effect of stabilizing exercises and acupuncture on postpartum sacroiliac pain.Methods: Forty multiparous women with sacroiliac joint pain (SIJP), were included, aged 25 to 35 years, BMI not exceed 30kg/m², parity less than 3 times, and delivered normally, they're assigned into two equal groups. Group (A) performed stabilizing exercises for lumbo-pelvic muscles and acupuncture. Group (B) received only acupuncture, were performed three times per week for two months (24sessions). The assessment throughout the present pain intensity (PPi) and the Oswestery disability questionnaire before and after the treatment.Results: It revealed a significant decrease in the PPi scores and a significant improvement in functional disability in both groups (A,B). Group (A) showed a significant decrease in the PPi scores and significant improvement in functional disability with percentage of improvement was 75%% & 62.5% respectively more than in the group (B) the percentage of improvement was 40% & 46.7% respectively.Conclusion: These results indicate that the lumbo- pelvic stabilizing exercises in conjunction with acupuncture were effective adjunct methods in alleviating postpartum sacroiliac joint pain.